Research of influence of the mechanism of forecasting of the traffic on quality of system of adaptive management of the switchboard - Муранов, О. С.; Кочергін, Ю. А.; Чуприн, В. М. (Problems of Informatization and Control, 2009)
It is analysed system mistakes of adaptive management of the mechanism of redistribution of throughput of the batch switchboard between ports. For reduction of mistakes of management use of forecasting in a contour of management of the mechanism of redistribution is is offered. Introduction of the mechanism of forecasting allows to reduce, and under certain conditions and to eliminate mistakes of management which lead to losses of packages